2000
DOI: 10.1634/stemcells.18-1-53
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mouse Dendritic Cells from Lineage‐Negative c‐kit<lowPluripotent Hemopoietic Stem Cells In Vitro

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Among these cytokines, only IL-3, but not FLT3-L, SCF, or IL-6, could expand HPs, a finding in agreement with those of previous reports [5], [6], over 10 days after floating cultivation in a low cell binding plate (Fig. 1a).…”
Section: Resultssupporting
confidence: 93%
“…Among these cytokines, only IL-3, but not FLT3-L, SCF, or IL-6, could expand HPs, a finding in agreement with those of previous reports [5], [6], over 10 days after floating cultivation in a low cell binding plate (Fig. 1a).…”
Section: Resultssupporting
confidence: 93%
“…Investigations of c-kit function in dendritic cells have lagged because in-vitro development of bone-marrow-derived dendritic cells (BMDCs) from HSCs earmarked c-kit as being stem-cell-specific. These studies [2729] reported decreased c-kit expression upon dendritic cell development and maturation in line with the general profile of c-kit loss upon HSC differentiation. In fact, tissue dendritic cells do show minimal expression of this receptor.…”
Section: C-kit Has Important Functions In Different Cell Types Includmentioning
confidence: 55%
“…Many studies have elucidated the role of cytokines required for the differentiation or maturation of DCs in vitro. [4][5][6][7] Although granulocyte-macrophage colony-stimulating factor (GM-CSF) is known to be essential for DC generation from BM progenitor cells, [8][9][10] the mediators responsible for subsequent differentiation and maturation of DCs are not fully understood. As for recruitment to the lymphoid tissues, recent studies proved that chemokines expressed in the lymphoid organs, including secondary lymphoid tissue chemokine (SLC, CCL21) and Epstein Barr virus-induced molecule 1 ligand chemokine (ELC, CCL19), play an important role in mobilization of mature DCs to the spleen and LN.…”
Section: Introductionmentioning
confidence: 99%